Leadership excellence - Williams, Pat, 1940- (Barbour Pub, 2012)
Succeeding at leadingfind out how in Pat Williams' ultimate leadership book. You'll learn the essential skills to help your people achieve, in whatever setting you serve. Leadership Excellence draws upon leaders of history and the presentin business, sports, religion, and politicsto distill great principles that apply to leaders of any age, background, and setting. You'll benefit from years of experience and hundreds of interviews by Williams, senior vice president of the NBA's Orlando Magic, as you're exposed to leadership's seven sides: vision, communication, people skills, character, competence, boldness, and most importantly, a servant's heart.